Evaluating a modified behavioral skills training procedure for teaching poison prevention skills to children with autism. Issue 2 (22nd November 2020) - Petit‐Frere, Paula; Miltenberger, Raymond G.
Abstract : Accidental poisonings can occur for children with disabilities as a result of ingesting household products, such as medications and cleaning chemicals, if the products are not stored safely. Behavioral approaches such as behavioral skills training (BST) have been used in previous research to teach safety skills to children with disabilities. However, research suggests that BST is not always effective for teaching safety skills to children with and without disabilities. Thus, the purpose of this study was to evaluate the efficacy of a modified BST package that incorporated a system of least prompts. A nonconcurrent multiple baseline design across participants was used to evaluate the effects of intervention with three 6‐8‐year‐old children with autism. Results showed that BST with the prompt sequence increased poison prevention skills for all 3 participants and the skills maintained at follow‐up.